Self-Governing Regions in Slovakia: Spatial Differentiation and Perception of Socio-Cultural Identity by Local and Regional Officials - Bucher, Slavomír; Ištoková, Miroslava (Geografie, 2015)
This article seeks to contribute to the discussion about the concept of socio-cultural identity in geographical science. Its main aim is to present the concept of local and regional identity, first as a significant source of sustainable national wealth and secondly as an effective tool for regional development in Slovakia. Slovakia consists of several kinds of regions at the sub-national level, represented by historical areas, small ethnographic regions and various administrative units. Their hierarchy derives from their former historical role, current administrative function, and their regional importance. The outputs of this survey indicate regional disparities in the so-called soft factors involved in the development of social identity among Slovakia’s self-governing regions. In addition, the article discusses the need for a more comprehensive approach, directly linking ethnographic, geographical and sociological methods.